Nursing performance in the prevention of urinary infections associated with overload bladder problems in the adult intensive care unit (Research, Society and Development, 2023)
The present study aims to identify the importance of nursing care in urinary infections associated with indwelling urinary catheters in the A-ICU. This descriptive research has an integrative bibliographic source and a qualitative approach. Data collection took place through secondary data: integrative literature review and documentary research. Processing took place using information made available through a search for scientific articles published between 2012 and 2021 in the databases Lilacs (Latin American and Caribbean Literature in Health Sciences), SciELO (Scientific Electronic Library Online), VHL (Virtual Health Library) and Google Scholar. We selected 15 articles for the survey of the bibliographic sample, taking into account those with greater importance for the object of study. Thus, the importance of nurses in the prevention of ACUTI is evident, using simple methods such as hand hygiene and updating their knowledge, which can influence the prevention, monitoring and complications of ACUTI.